Real role models : successful African Americans beyond pop culture - Spearman, Joah, 1983- (University of Texas Press, 2010)
All young people need good role models, and black youth especially need positive and real examples beyond the famous and wealthy people they see on SportsCenter highlights and MTV Cribs. While success as a celebrity athlete or entertainer may seem like an achievable dream, the reality is that young African Americans have a much greater chance of succeeding in the professions through education and hard work--and a mentor to show them the path. Real Role Models introduces high school and college-age African Americans to twenty-three black professionals who have achieved a high level of success in their chosen fields and who tell their stories to inspire young people to pursue a professional career and do the work necessary to achieve their dreams.